IMPLEMENTASI SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP PROSES PENGADAAN BARANG DAN JASA PADA SATUAN POLISI PAMONG PRAJA KOTA BOGOR - Purwanto, Edi; Setiawan, Ade Budi (Jurnal Akunida, 2015)
This study aimed to analyze the internal control system against government goods and services procurement process on Satuan Polisi Pamong Praja Bogor city, researchers used the method is deskristif comparative where this research is to compare. Done by comparing the Government Regulation No. 60 Year 2008 concerning Internal Control Systems Government by Presidential Decree No. 4 of 2015 On Procurement of Government Goods/Services in the process of procurement of goods and services to Satuan Polisi Pamong Praja Bogor city. Results of the analysis showed was conducted in accordance with Government Regulation No. 60 Year 2008 concerning government internal control system which includes control environment, risk assessment, control activities, information and communication, and monitoring but still there are indicators of vulnerability is discovered that the lack of human resources who possess a certificate of procurement goods and services in order to supervise the activities can be more awake quality and work in accordance with the schedule already planned. This is done in order to achieve effective financial management and efficient.